Relationship between muscle strength in various isokinetic movements and kick performance among soccer players - Masuda, K.; Kikuhara, N.; Demura, S.; Katsuta, S.; Yamanaka, K. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The present study was carried out to examine relationships between muscular strength and ball velocity with respect to 3 different approach angles and focussing on both the kicking leg and the supporting leg among soccer players of different skill levels. Methods: Fourteen university soccer players were divided into 2 groups (superior group, average group), and kicked the ball with maximal effort towards a target 15 m away. The angles of approach to the stationary ball varied in 3 directions (free, 1.57, 2.36 rad to the kick direction). Mean ball velocity and the success rate of striking the target with the ball were measured. Maximal isokinetic and concentric muscular strength was measured in terms of motions of the knee Ext/Flex, hip Ext/Flex and hip Abd/Add using an isokinetic dynamometer. Results: The mean ball velocity at free and 1.57 rad approach angles related significantly with hip Add but not with knee Ext strength for the kicking leg. In contrast, the ball velocity at an approach angle of 2.36 rad significantly correlated with knee Ext and hip Flex of the kicking leg. Although ball velocity at the free and the 1.57 rad approach angles showed no relation to strength of the supporting leg, the ball velocity at the 2.36 rad approach angle showed a significant relationship with knee Flex, hip Ext and hip Abd strength of the supporting leg. Furthermore, the superior group had more strength variables related to performance than the average group. Conclusion: Different approach angles would alter the requirement on muscle strength potential of both kicking and supporting leg during kicking. Especially an angled approach to the kick direction could require greater hip extension and abduction strength on the supporting leg for a higher capability for stabilizing body balance. Besides, skill level may alter the importance of muscle strength requirement to kick performance.